The Propensity to Leave The Organization Among the Staff of Hotel Industry in Kuala Lumpur - Lim, Lai Choon (2002)
Competence workers play a major role in boosting the hotel industries. However, high staff turnover tends to inhibit their growth. Therefore it is rather important that the managers identify and understand the factors related to the propensity to leave. The general objective of the study is to examine the predictors of hotel staff propensity to leave; and the mediating role of job satisfaction and organizational commitment. Specifically it aims to examine the relationship of research variables; and whether job satisfaction and organizational commitment mediate the effect of independent variables on the dependent variable. The study was conducted in the selected hotels in Kuala Lumpur by using a questionnaire. A total of 238 valid responses were obtained. Frequencies, descriptive, regression analysis, correlation and path analysis were used to analyze the data There are two parts in the findings, the relationship of study variables and the role mediating variables In the first part, findings show that self-esteem, emotional intelligence, role conflict, role ambiguity, work overload, perceived empowerment, perceived career advancement and perceived leader -staff relationship are significantly related to job satisfaction All these variables are also found to be significantly related to propensity to leave and organizational commitment except for emotional intelligence Job satisfaction and organizational commitment are also related to propensity to leave In the second part, findings show that job satisfaction mediates the effect of emotional intelligence, role ambiguity, work overload, perceived empowerment and perceived leader-staff relationship on propensity to leave Organizational commitment mediates the effect of self-esteem, role conflict, role ambiguity, work overload, perceived empowerment, perceived career advancement and perceived leader-staff relationship on propensity to leave